A Model of Global Beverage Markets. (August 2020) - Wittwer, Glyn; Anderson, Kym
Abstract: This article describes a new empirical model of the world's markets for alcoholic beverages and, to illustrate its usefulness, reports results from projections of those markets from 2016–2018 to 2025 under various scenarios. It not only revises and updates a model of the world's wine markets (Wittwer, Berger, and Anderson, 2003 ), but also adds beer and spirits so as to capture the substitutability of those beverages among consumers. The model has some of the features of an economy-wide computable general equilibrium model, with international trade linking the markets of its 44 countries and seven residual regions. It is used to simulate prospects for these markets by 2025 (business-as-usual), which points to Asia's rise. Then two alternative scenarios to 2025 are explored: one simulates the withdrawal of the United Kingdom from the European Union (EU); the other simulates the effects of the recent imposition of additional 25% tariffs on selected beverages imported by the United States from several EU member countries. Future applications of the model are discussed in the concluding section. (JEL Classifications: C53, F11, F17, Q13)